2013
DOI: 10.1167/iovs.12-11294
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Human Corneal Epithelial Cells From TNF-α–Induced Disruption of Barrier Function by Rebamipide

Abstract: Rebamipide protects corneal epithelial cells from the TNF-α-induced disruption of barrier function by maintaining the distribution and expression of ZO-1 as well as the organization of the actin cytoskeleton. Rebamipide is, thus, a potential drug for preventing or ameliorating the loss of corneal epithelial barrier function associated with ocular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 49 publications
3
49
0
Order By: Relevance
“…The aim of this study was to evaluate taste-masking effect of CGA on bitter drugs using taste sensor measurements and surface plasmon resonance (SPR) analysis of CGA-drug interactions. Six different bitter drugs were used: amlodipine besylate (AMD), [19][20][21] diphenhydramine hydrochloride (DPH), 22) donepezil hydrochloride (DNP), 6) rebamipide (RBM), 18,23,24) diclofenac sodium (DCF) 25) and etodolac (ETD). 25) These drugs are well-established as bitter medicines and are widely used in clinical practice.…”
Section: Taste-masking Effect Of Chlorogenic Acid (Cga) On Bitter Drumentioning
confidence: 99%
“…The aim of this study was to evaluate taste-masking effect of CGA on bitter drugs using taste sensor measurements and surface plasmon resonance (SPR) analysis of CGA-drug interactions. Six different bitter drugs were used: amlodipine besylate (AMD), [19][20][21] diphenhydramine hydrochloride (DPH), 22) donepezil hydrochloride (DNP), 6) rebamipide (RBM), 18,23,24) diclofenac sodium (DCF) 25) and etodolac (ETD). 25) These drugs are well-established as bitter medicines and are widely used in clinical practice.…”
Section: Taste-masking Effect Of Chlorogenic Acid (Cga) On Bitter Drumentioning
confidence: 99%
“…It also causes a decrease in the secretion of inflammatory cytokines. A 2 % ophthalmic solution of rebamipide increases tear stability markedly and causes an increase in MUC5 mRNA expression on the ocular surface [97,98]. Ohguchi et al [99] have shown the anti-inflammatory effect of rebamipide on tears, as well as the antioxidant effect on the conjunctiva.…”
Section: Biological Agentsmentioning
confidence: 99%
“…Rebamipide also decreases cytokine expression in human corneal epithelium by treating the barrier dysfunction related to TNF-a [99]. Kimura et al have shown that rebamipide blocks the barrier dysfunction and protects Z01 expression [98].…”
Section: Biological Agentsmentioning
confidence: 99%
“…Immunoblot analysis of total or phosphorylated forms of ERK, p38 MAPK, JNK, and IjB-a, as well as of RAR-a, RAR-b, and RAR-c, was also performed as described previously. 20 In brief, cells were lysed in a solution containing 50 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1 mM EDTA, 5 mM NaF, 1% Nonidet P-40, 0.5% sodium deoxycholate, 0.1% SDS, 1 mM Na 3 VO 4 , and 1% protease inhibitor cocktail, and the cell lysates (10 lg protein) were subjected to immunoblot analysis.…”
Section: Immunoblot Analysismentioning
confidence: 99%